Behavior Therapy for a Pregnant Woman with Obsessive-Compulsive Disorder - AOKI, Shouzou; MIYAZAKI, Tetsuji; NAKAGAWA, Akiko (Japanese Journal of Behavior Therapy, 2014)
Pregnancy and childbirth are well-known risk factors for the onset or worsening of obsessive-compulsive disorders. However, there are few reports of behavioral approaches to these cases, especially in Japan. In the present study, a 28-year-old pregnant woman with obsessive-compulsive disorder was successfully treated by behavior therapy consisting primarily of exposure and response prevention without medication. After marriage, the woman came to have an obsessive-compulsive disorder which worsened after pregnancy. At her first medical examination, the present authors observed that she disinfected the soles of her feet and the floor of the lavatory, took photographs and made detailed notes of her own actions, and checked her actions when she went to the lavatory. In addition, she related that her obsessions interfered with housework including cooking: "I must spread dirt and germs." She was given behavior therapy consisting primarily of exposure and response prevention once a week for 12 weeks. Her obsessive-compulsive symptoms gradually decreased. No obsessive-compulsive symptoms were observed at the time of childbirth, and she was able to do housework and take care of her baby. At a half-year follow-up medical examination, the improvement was observed to have been maintained.